Strategi Pengembangan Ekonomi Kreatif pada Subsektor Wisata Kuliner Berbasis Kearifan Lokal di Kota Sampang - S Anugrahini Irawati; Riyan Bagus Nugroho (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The creative economy has become one of the fastest growing sectors in Indonesia, making a significant contribution to the local economy. Culinary tourism, one of the sub-sectors of the creative economy, plays a major role with the potential for developing culinary tourism based on local wisdom in various regions, including Sampang, Madura. This study aims to determine the problems being faced, and how the creative economy development strategy is in the culinary tourism sub-sector based on local wisdom in the city of Sampang. The method used in this study is a qualitative descriptive research method. The findings of this study are expected to help formulate an effective strategy to strengthen the creative economy in Sampang in the culinary tourism sub-sector. The results of the study show that the problems faced by culinary entrepreneurs based on local wisdom in the city of Sampang include the lack of innovation in product development and interior design, the lack of optimal use of technology as a promotional medium, and the limited number of skilled human resources. The development strategy carried out by innovating in product packaging and taste, maintaining product uniqueness, maintaining product authenticity, while creating new innovations in presentation and packaging.